Effects of Exercise-Cognition Integrated Training for Enhancement (ExCITE) program on gait speed and postural stability in sedentary older adults - Ong, Hui Lin (Nanyang Technological University, 2019)
Faced with a worldwide rapid increase in aging population, supportive solutions for increasing overall healthy-life expectancy of older adults are at high demand. Statistics of the emergency department in National University Hospital (NUH), identified accidental falls as the key mechanism for sustained trauma in older adults. The objective of the current study is to investigate the training effect of a 6-weeks Exercise-Cognition Integrated Training for Enhancement (ExCITE) training program on fall risk indicators such as Gait speed and One-legged stance (OLS) postural stability. It was hypothesized that the Intervention group will demonstrate higher performance in the outcome parameters compared to the Control group. A total of 20 older adults were recruited and randomly assigned to either the Intervention (3 males, 7 females; M age = 63.8, SD = 5.92) or Control group (2 males, 8 females; M age = 63.70, SD = 7.36). Gait speed and OLS postural stability were assessed over five-time points (Pre – 3rd Session – 6th Session – 9th session – Post) throughout the 6-weeks training program. Repeated measures randomized group design was applied with alpha level set at .05 for all statistical tests. Results showed no significant difference in gait speed and OLS postural stability performance between participants in the Intervention and Control group. ExCITE task performance accuracy (%) however presented a significant improvement (p = .036). In conclusion, findings were unable to demonstrate any real-training benefits on motor performance effected by the ExCITE training program. More comprehensive and intricate data analysis method is proposed to increase sensitivity towards recording potential training effect.